The natural history of glycogen storage disease type Ib in England: A multisite survey. Issue 1 (24th January 2021) - Halligan, Rebecca; White, Fiona J.; Schwahn, Bernd; Stepien, Karolina M.; Kamarus Jaman, Nazreen; McSweeney, Mel; Kitchen, Steve; Gribben, Joanna; Dawson, Charlotte; Lewis, Katherine; Cregeen, David; Mundy, Helen; et al.
Abstract: Glycogen storage disease type Ib (GSDIb) is characterized by hepatomegaly and fasting hypoglycaemia as well as neutropaenia and recurrent infections. We conducted a retrospective observational study on a cohort of patients with GSDIb across England. A total of 35 patients, with a median age of 9.1 years (range 1‐39 years), were included in the study. We examined the genotype and phenotype of all patients and reported 14 novel alleles. The phenotype of GSDIb in England involves a short fasting tolerance that extends into adulthood and a high prevalence of gastrointestinal symptoms. Growth is difficult to manage and neutropaenia and recurrent infections persist throughout life. Liver transplantation was performed in nine patients, which normalized fasting tolerance but did not correct neutropaenia. This is the first natural history study on the cohort of GSDIb patients in England. Abstract :